2004
DOI: 10.1002/hec.907
|View full text |Cite
|
Sign up to set email alerts
|

The role of consumer knowledge of insurance benefits in the demand for preventive health care among the elderly

Abstract: In 1992, the United States Centers for Medicare and Medicaid Services (CMS) introduced new insurance coverage for two preventive services--influenza vaccinations and mammograms. Economists typically assume transactions occur with perfect information and foresight. As a test of the value of information, we estimate the effect of consumer knowledge of these benefits on their demand. Treating knowledge as endogenous in a two-part model of demand, we find that consumer knowledge has a substantial positive effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 11 publications
3
37
0
1
Order By: Relevance
“…In line with a number of previous papers relying on observational data (Kenkel, 1990;Hsieh and Lin, 1997;Parente, Salkever and DaVanzo, 2005;Nuscheler and Roeder 2014;Maurer, 2009), our results stress the high relevance of information for preventive decisions. More precisely, our results suggest that an exogenous informational shock induced by home delivery of the letter strongly affects preventive decisions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with a number of previous papers relying on observational data (Kenkel, 1990;Hsieh and Lin, 1997;Parente, Salkever and DaVanzo, 2005;Nuscheler and Roeder 2014;Maurer, 2009), our results stress the high relevance of information for preventive decisions. More precisely, our results suggest that an exogenous informational shock induced by home delivery of the letter strongly affects preventive decisions.…”
Section: Discussionsupporting
confidence: 91%
“…Previous papers that rely on observational data estimate a positive effect of information on preventive decisions (e.g. Hsieh and Lin, 1997;Parente, Salkever and DaVanzo, 2005). Nuscheler and Roeder (2014) recently showed for the case of influenza vaccination that well informed individuals have a much higher propensity to vaccinate than poorly informed individuals, highlighting the importance of information campaigns in public health policy.…”
Section: Introductionmentioning
confidence: 99%
“…Poor health decision-making depends on many factors such as lack of health knowledge, unsupportive spouse, lack of autonomy, etc. Many studies have shown that patients' limited health knowledge has a substantial negative effect on the use of health services (Hsieh and Lin, 1997;Parente et al, 2005;Waiswa et al, 2010). In the Indian context, Bhargava et al (2005) and Kumar and Dansereau (2014) found that health infrastructure, availability of drugs and the quality of care are important predictors of health care utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, unravelling the role of supply and demand factors is instrumental in identifying potential policy leverages for promoting vaccination and targeting intervention at either market side. To date, most of the health economics research on vaccination take-up has exclusively focussed on demand-side factors (see, for example, Ayyagari (2007a,b), Mullahy (1999) or Parente et al (2004)), with no formal attempt to separate the simultaneous influences of supply and demand. Yet, the abundance of asymmetric information in health care markets makes it all the more important to bring the supply side in from the cold.…”
mentioning
confidence: 99%